Ransam - random sample design for Ireland - Whelan, Brendan J. (Economic & Social Studies, 1979)
The purpose of this paper is to describe RANSAM , the computer-based system for drawing random samples from the Electoral Register, which has been developed over the past few years at ESRI. This system, which is updated each year by reference to the most recent Electoral Register, permits us to offer a sample selection service to those contemplating carrying out a survey on a local (e.g., regional) or national level. The computer costs in selecting samples are quite low, and the names and addresses can by typed at reasonable cost. Such samples have the advantage that we can ensure that the selected respondents have not cropped up in any of the surveys conducted by the ESRI in the current year. This paper first discusses the use of the Electoral Register as a sampling frame. It then goes on to describe the main features of RANSAM and the reasons why these features have been included. It should be noted that throughout the paper we are concerned with random or probability samples (i.e., samples in which the probability of inclusion of each element is calculable). Non-random samples (e.g., quota samples) can also be based on the present selection system. For instance, we sometimes use RANSAM to select a random sample of names and addresses as starting points for the interviewers and instruct them to call on the selected respondent and on, say, every twentieth house thereafter.
Keywords: Election analysis - Methodology; Economic and Social Research Institute (ESRI)